(untitled) - Chanda, Manas (Boca Raton, FL, 2009)
The book begins with a discussion of different types of molds and dies, including compression molding, injection molding, blow molding, thermoforming, reaction injection molding, extrusion, and pultrusion. It then covers spinning, casting, reinforcing, foaming, compounding, and coating processes as well as powder molding, adhesive bonding, and plastics welding techniques. The authors also explore the decoration of plastics, including painting operations, printing processes, hot stamping, in-mold decorating, embossing, electroplating, and vacuum metallizing. They conclude with an overview on key aspects of plastics recycling, developments in the field, and waste recycling problems.
Keywords: Plastics,Plastics; Recycling